Peran Pendapatan (SHU) dalam Meningkatkan Usaha Koperasi - Muhammad Fahmul Iltiham (Jurnal Istiqro, 2016)
In essence, the cooperative is a business entity, as a business entity that runs the cooperative business activities will generate revenue that will be enjoyed by the members and the cooperative itself. Revenue cooperative or often called SHU is one of the attractions for a person to become a member which can improve cooperative efforts. SHU cooperative magnitude sign cooperative has managed professionally. Thus increasing the SHU also increase the welfare and survival of members of the cooperative. Formulation of the problem in this research is factor-facto cause of the increase in SHU and how the role of income (SHU) in improving cooperative efforts in Al-Mumtaz. The purpose of this study was to determine the causal factors and the role of income (SHU) in improving cooperative efforts in Al-Mumtaz. The method used in this research is descriptive qualitative method, which the researchers describe the results of research by describing the state of the process, a particular event. The data obtained by the authors included primary data and secondary data conducted by collecting data with field study conducted by observation, interviews, documentation and literature. The results of this study indicate that factors that can increase the income of the cooperative (SHU) is the capital, the business volume, the participation of members, business unit, performance management and supervisors as well as the government. Then the increase in income of the cooperative (SHU) has increased each year, the increase can be seen from the capital increase and the volume of business on a cooperative. In this study, the role of income (SHU) for cooperative efforts among them is their cooperative business expansion with the opening of branches of business in the territory of Singosari and the addition of capital raised from member savings derived from the SHU members who entered as a deposit back. SHU obtained with the cooperative, the cooperative can cultivate through a fund set aside a reserve fund every year, and other funds not disbursed can be used as loan capital for increasing cooperative efforts.